Methane oxidation in industrial biogas plants: insights in a novel methanotrophic environment evidenced by pmoA gene analyses and stable isotope labelling studies - May, Tobias; Polag, Daniela; Keppler, Frank; Greule, Markus (Journal of biotechnology, 2018)
A broad methanotrophic community consisting of 16 different operational taxonomic units (OTUs) was detected by particulate methane monooxygenase A (pmoA) gene analyses of reactor sludge samples obtained from an industrial biogas plant. Using a cloning-sequencing approach, 75% of the OTUs were affiliated to the group of type I methanotrophs (γ-Proteobacteria) and 25% to type II methanotrophs (α-Proteobacteria) with a distinct predominance of the genus Methylobacter. By database matching, half of the total OTUs may constitute entirely novel species. For evaluation of process conditions that support growth of methanotrophic bacteria, qPCR analyses of pmoA gene copy numbers were performed during a sampling period of 70 days at varying reactor feeding scenarios. During the investigation period, methanotrophic cell counts estimated by qPCR fluctuated between 3.4×104 and 2×105 cells/mL with no distinct correlation to the organic loading rate, the amount of CH4, O2 and NH4-N. Methanotrophic activity was proofed even at low O2 levels (1%) by using stable carbon isotope labelling experiments of CH4 in batch experiments inoculated with reactor sludge. Supplementation of 13C labelled CH4 in the headspace of the reaction vials unambiguously confirmed the formation of 13C labelled CO2. Thus, industrial biogas reactors can be considered as a further methanotrophic habitat that exhibits a unique methanotrophic community which is specifically adapted to high CH4 and low O2 concentrations. To the best of our knowledge, our study is the first accurate detection and quantification of methanotrophic bacteria in industrial biogas reactors.
Gesehen am 05.09.2019